Implementasi Pendekatan Problem Posing Dengan Macromedia Flash Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Shindy Ekawati; Fahrul Basir; Karmila Karmila; Sukmawati Sukmawati; Fitriani A (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study aims to analyze students' mathematical problem solving abilities applying the problem posing approach with Macromedia Flash in class X SMAN 1 Luwu. This is an experimental research with a quasi-experimental form. This study used a one group pretest posttest design. This design uses an initial test (pretest) then after being given the treatment, another measurement (posttest) is carried out. The population in the study was all 12 classes of X SMA 1 Luwu students. The sample in this study was class X MIPA 7 at SMAN 1 Luwu with a total of 25 students. The sampling technique used in this study was purposive sampling. Data analysis techniques used in this study are descriptive statistical analysis and inferential statistics. The type of t-test used is the one sample t-test. The results showed that students' mathematical problem-solving skills before applying the problem posing approach with Macromedia Flash in class X SMAN 1 Luwu, on average were in the medium category. The students' mathematical problem solving ability after applying the problem posing approach with Macromedia Flash in class X SMAN 1 Luwu, on average is in the high category. There was an increase in the mathematical problem solving ability of class X students of SMAN 1 Luwu after applying the problem posing approach with Macromedia Flash.